PENERAPAN MODEL PEMBELAJARAN ARTIKULASI DALAM MENINGKATKAN HASIL BELAJAR EKONOMI BISNIS SISWA KELAS XII DI SMK PGRI SUMBER AGUNG OKU TIMUR - Sudawan Supriadi; Isnul Farida (PT. Intelek Cendikiawan Nusantara, 2024)
Low student participation is an obstacle in the learning process. The business economic learning outcomes of class XII SMK PGRI Sumber Agung still have not reached classical completeness. The reason is that students are not active in classroom learning. To anticipate these problems, the alternative used is through the articulation learning model, because this model is a learning technique so that students can work together with peers. The subjects of this study were XII grade students of SMK PGRI Sumber Agung in the 2023/2024 academic year totaling 20 students. This research is a classroom action research conducted collaboratively between teachers and researchers. This research was carried out in two cycles, namely cycle I, and cycle II. Data collection techniques in this study were observation, tests, and documentation. The data obtained were then analyzed descriptively quantitatively in each cycle. To determine student learning outcomes on the material studied, test questions were used which were then analyzed using the standard reference for the minimum completeness criteria (KKM) >70. From the data analysis of the research results it can be concluded that, (1) learning by using the articulation learning model can improve the learning outcomes of XII grade students of SMK PGRI Sumber Agung on the subject of money and banking. This can be seen from the student learning outcomes in the pre-cycle 55%, in cycle I 70%, and cycle II 90%. (2) Learning by using the articulation learning model can improve the economic learning outcomes of XII grade students at SMK PGRI Sumber Agung, Kecamatan Buay Madang, Kabupaten OKU Timur, this can be seen from the average economic learning outcomes that are increasing and the level of completeness is getting higher.